2018
DOI: 10.1029/2018jg004520
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Droughts Responsible for Dramatic Reductions of Terrestrial Net Carbon Uptake Over North America in 2011 and 2012

Abstract: Recently, severe droughts that occurred in North America are likely to have impacted its terrestrial carbon sink. However, process-based understanding of how meteorological conditions prior to the onset of drought, for instance warm or cold springs, affect drought-induced carbon cycle effects remains scarce. Here we assess and compare the response of terrestrial carbon fluxes to summer droughts in 2011 and 2012 characterized by contrasting spring conditions. The analysis is based on a comprehensive ensemble of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…Despite these difficulties, several studies have attempted to quantify ecosystem legacy effects by leveraging approaches such as eddy covariance (Shen et al 2016; Yang et al 2016; He et al 2018), remote sensing products (Gazol et al 2018, Wu et al 2018, Yu et al 2017), ecosystem models (Shen et al 2016), model intercomparison projects (Anderegg et al 2015a, Kolus et al 2019), or a diverse array of the aforementioned data sources (Schwalm et al 2017; Kannenberg et al 2019c). While these studies quantify legacy effects at different scales, using different methods, in a wide variety of ecosystem processes, one commonality is clear: legacy effects in C uptake at the ecosystem scale seem to be smaller and shorter than those in tree rings.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these difficulties, several studies have attempted to quantify ecosystem legacy effects by leveraging approaches such as eddy covariance (Shen et al 2016; Yang et al 2016; He et al 2018), remote sensing products (Gazol et al 2018, Wu et al 2018, Yu et al 2017), ecosystem models (Shen et al 2016), model intercomparison projects (Anderegg et al 2015a, Kolus et al 2019), or a diverse array of the aforementioned data sources (Schwalm et al 2017; Kannenberg et al 2019c). While these studies quantify legacy effects at different scales, using different methods, in a wide variety of ecosystem processes, one commonality is clear: legacy effects in C uptake at the ecosystem scale seem to be smaller and shorter than those in tree rings.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 25% of global anthropogenic CO 2 emissions are counteracted by terrestrial ecosystems [1], but the terrestrial carbon cycle is easily affected by climate extremes. The increase in the frequency and intensity of climatic extremes predicted by global climate models in the 21st century [2] indicated that anthropogenic activities are changing the climate [3], which has an evident impact on the composition, structure and functions of terrestrial ecosystems and indirectly alters the terrestrial carbon balance [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the positive anomalies of temperature during flash droughts might also increase ecosystem respiration and further intensify the carbon loss of terrestrial ecosystem [ 29 ]. He et al [ 20 ] found that the enhanced respiration caused more carbon loss for grasslands and croplands during the 2012 flash drought over North America. The responses of LAI occur during 79% of the flash droughts, indicating the structural changes of the ecosystem during flash droughts.…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystem photosynthesis and respiratory processes can be suppressed when vegetation is under water stress [ 33 ] and GPP is the total ecosystem carbon uptake representing the dynamics of vegetation photosynthetic functioning. NPP is the discrepancy between GPP and autotrophic respiration integrating the impacts of drought on photosynthesis and respiration [ 20 ]. LAI is the green leaf area per unit ground area, which can be used to detect changes of vegetation state (e.g., defoliation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation